CRISPR/Cas9‐Based Dystrophin Restoration Reveals a Novel Role for Dystrophin in Bioenergetics and Stress Resistance of Muscle Progenitors. (18th November 2019) - Matre, Polina R.; Mu, Xiaodong; Wu, Jianbo; Danila, Delia; Hall, Mary A.; Kolonin, Mikhail G.; Darabi, Radbod; Huard, Johnny
Abstract: Although the lack of dystrophin expression in muscle myofibers is the central cause of Duchenne muscular dystrophy (DMD), accumulating evidence suggests that DMD may also be a stem cell disease. Recent studies have revealed dystrophin expression in satellite cells and demonstrated that dystrophin deficiency is directly related to abnormalities in satellite cell polarity, asymmetric division, and epigenetic regulation, thus contributing to the manifestation of the DMD phenotype. Although metabolic and mitochondrial dysfunctions have also been associated with the DMD pathophysiology profile, interestingly, the role of dystrophin with respect to stem cells dysfunction has not been elucidated. In the past few years, editing of the gene that encodes dystrophin has emerged as a promising therapeutic approach for DMD, although the effects of dystrophin restoration in stem cells have not been addressed. Herein, we describe our use of a clustered regularly interspaced short palindromic repeats/Cas9‐based system to correct the dystrophin mutation in dystrophic ( mdx ) muscle progenitor cells (MPCs) and show that the expression of dystrophin significantly improved cellular properties of the mdx MPCs in vitro. Our findings reveal that dystrophin‐restored mdx MPCs demonstrated improvements in cell proliferation, differentiation, bioenergetics, and resistance to oxidative and endoplasmic reticulum stress. Furthermore, our in vivo studies demonstrated improved transplantation efficiency of the corrected MPCs in the muscles of mdx mice. Our results indicate that changes in cellular energetics and stress resistance via dystrophin restoration enhance muscle progenitor cell function, further validating that dystrophin plays a role in stem cell function and demonstrating the potential for new therapeutic approaches for DMD. Stem Cells 2019;37:1615–1628 Abstract : Lack of dystrophin in muscle myofibers is the central cause of Duchenne muscular dystrophy. Accumulating evidence suggests that Duchenne muscular dystrophy may also be a stem cell disease. In this study, the authors restored dystrophin in muscle progenitors using gene editing and enhanced their function, suggesting a novel role of dystrophin in muscle progenitor and potentially new therapeutic approaches for Duchenne muscular dystrophy.